Analysis of the Implementation of Income Tax Article 24 in Reducing International Tax Burdens - Aisyah Winanda Harahap; M.G. Fahluzi; Wahyu Abdul Aziz P; Windi Ayunanda (International Journal of Economic Research and Financial Accounting, 2025)
In the contemporary era of globalization, cross-border economic activities have resulted in an elevated risk of double taxation for taxpayers who generate income from abroad. In Indonesia, this issue is addressed through the provisions of Income Tax Article 24. However, its implementation still faces various administrative and technical obstacles. The objective of this study is to analyze the impact of the implementation of PPh Article 24 on the reduction of the international tax burden on domestic taxpayers. The present study employs a qualitative approach, utilizing a literature review method to examine legal sources, academic articles, and company reports from the years 2021–2025. The findings of the study suggest that Income Tax Article 24 possesses considerable potential in the reduction of double taxation. However, its effectiveness is contingent upon several factors, including the completeness of documentation, the utilization of international tax agreements, and the readiness of the reporting system. The findings also indicate that technology integration and improved taxpayer education are important factors in supporting the success of this policy. The findings of this study underscore the significance of implementing administrative reforms and the digitalization of the tax system.